Successful salvage of upper extremity following severe crush injury associated with vascular compromise using a supra thin free anterolateral thigh flap - Jangra, Mahesh; Kumar, Ajay; Sharma, Nipun; Singh, Heishnam S.; Gupta, Tarush; John, Jerry R. (International Surgery Journal, 2024)
Traumatic injuries of the upper limbs can often result in serious and challenging wounds involving multiple compartments such as skin, bone, tendons and neurovascular structures. These type of injuries of the upper extremity pose several challenges to the plastic surgeon. The main difficulty is to provide a stable, long lasting and aesthetically acceptable coverage that enables joints excursion so that patient can return to work at the earliest. Here, we present a case of 45 years old gentlemen who sustained severe crush injury associated with avulsed radial and ulnar artery of left upper limb following road traffic accident. At presentation, there was no pin prick in his hand and hand was pale. At first surgery, hand was revascularized using a vein graft in radial artery and skin grafting was done over the forearm defect as a temporary cover. After 12 hours, when the viability of hand was reassured, the defect was covered with free supra thin anterolateral thigh (ALT) flap. Patient’s hand and flap both survived and he was discharged in a satisfactory condition.